Marine actinomycetes from Malaysia marine environments with antagonistic potential - Zainal Abidin, Zaima Azira; Ahmad, Asmat; Usup, Gires; Khan Chowdhury, Ahmed Jalal (Desalination Publications, 2021)
Marine actinomycetes have garnered the attention of researchers worldwide due to their ability to produce unique and novel bioactive compounds. This study aimed at assessing the diversity and antagonistic potential of marine actinomycetes isolated from Langkawi Island, Kedah and Tioman Island, Johor. In a total of 215 isolates were successfully recovered of which 52% were obtained from Starch–yeast Extract Agar (SYE), 31.4% from Marine Agar (MA) and 16.3% from Actinomycetes Isolation Agar. Fourteen isolates were found to be positive of Polyketide Synthase Type I (PKS-I) and/or Non-ribosomal Peptide Synthetases (NRPS) genes and these isolates were then subjected to antimicrobial evaluation test against 3 Gram-positive bacteria – Staphylococcus aureus, Methicillinresistant S. aureus, Bacillus subtilis; 4 Gram-negative bacteria – Escherichia coli, Pseudomonas aeruginosa, Proteus mirabilis, Serratia marcescens; and 2 fungi – Candida albicans, Candida parapsilosis. Most isolates were able to inhibit at least one test microorganism. There is, however, no direct correlation between the presence of the biosynthetic genes and antagonistic potential as demonstrated by the lack of antimicrobial activity though PKS-I and/or NRPS genes were present. Molecular identification using the 16S rRNA gene revealed 10 isolates belonging to the genus Streptomyces and each representative of the genera Actinomadura, Rhodococcus, Gordonia and Salinispora. Among the isolates, Streptomyces sp. T55 is a potent antibacterial actinomycete while Streptomyces sp. T109 is a good antifungal agent. Further characterization of marine actinomycetes was conducted using scanning electron microscopy, culture characteristics on several media (SYE, MA, Potato Dextrose Agar, ISP2, ISP3, ISP4, Czapek Agar), NaCl tolerance and carbon sources utilization profile using BIOLOG. Findings from this study demonstrate the potential of Malaysia’s marine environment as a new resource of actinomycetes with biosynthetic capabilities which can be further explored for the development of the natural product.